Factors Influencing Complete Basic Immunization Coverage among Infants in Lubuk Siam Village: A PRECEDE-Based Approach - Eva Mayasari; Riska Epina Hayu; Wilker Helary (Journal of Health Education, 2026)
Background: Immunization coverage in Indonesia declined, with most provinces, including Riau, missing the Ministry of Health's strategic plan targets. In Lubuk Siam Village, Riau, community awareness of the importance of immunization was low. A 2023 survey showed that only 13% of toddlers were immunized.Methods: This mixed-method study utilized a sequential exploratory design. It began with the collection of qualitative data, which was then followed by quantitative data to enhance the findings. The study was conducted from May to September 2025 in Riau, Indonesia. The target population consisted of all mothers with toddlers aged 0 to 60 months. A total of 113 mothers participated in the study. Results: Bivariate analysis showed that family support (p = 0.031), knowledge (p = 0.004), and attitude (p < 0.001) were significantly associated with immunization status. In the final multivariable model, attitude was the strongest predictor of immunization status (AOR = 9.11; p < 0.001). Qualitative findings identified parental concerns about vaccine side effects, lack of paternal support, low maternal education, weak community leadership, limited health promotion activities, and family-centered decision-making as barriers to immunization. Conclusions: Maternal attitude was the most influential factor associated with immunization status. Family support, community influences, and health education were identified as key factors affecting immunization uptake. Strengthening family engagement and health promotion programs may improve immunization coverage